Role of Ferroptosis in Non-small Cell Lung Cancer and Progress of Traditional Chinese Medicine Intervention - Xiaoqi GUO; Tianqi WANG; Jinchan XIA; Huahui ZENG; Wenbo SHI (Chinese Journal of Lung Cancer, 2024)
Non-small cell lung cancer (NSCLC) is one of the malignant tumors with high morbidity and mortality worldwide. Ferroptosis is a new type of programmed cell death caused by abnormal accumulation of iron-dependent reactive oxygen species (ROS) leading to lipid peroxidation. It involves the balance between iron metabolism, lipid metabolism, oxygen free radical reaction and lipid peroxidation. Recent studies have found that ferroptosis is closely related to the occurrence and development of NSCLC. Due to the emergence of chemotherapy resistance and radiotherapy resistance in the treatment of NSCLC, there is an urgent need to develop new effective drugs and treatment strategies. Traditional Chinese medicine has unique advantages in the prevention and treatment of NSCLC due to its multi-targets and minimal side effects. In this review, we summarize the mechanism of ferroptosis in NSCLC, and discuss the research status of active ingredients of traditional Chinese medicine, single-herb traditional Chinese medicine and Chinese herbal compounds in the intervention of NSCLC through ferroptosis, in order to provide a new theoretical basis for the research of ferroptosis pathway and the prevention and treatment of NSCLC by targeted ferroptosis of traditional Chinese medicine.